ANZUS and Australia's Security: Australian Attitudes, September 1984 (ADA Dataverse, 2018)
Topics in this survey include: ANZUS; support for ANZUS; support for variety of forms of defence co-operation; US or Australia benefits more from ANZUS; Australian access under ANZUS to US technology, training and military hardware; ANZUS and risk of attack of Australia; trust in US to come to Australia's defence; visits by US warships carrying nuclear weapons; cost of Australian defence if not in ANZUS; ability of Australia to defend itself; US would come to Australia's defence if not an ally; joint facilities prevent nuclear war and increase Western country's security; joint facilities and risk of attack of Australia; benefits/risks joint facilities; continue in ANZUS alliance; countries threatening Australia's security now and in 5 years; strategies for securing Western security; confidence in the ability of the US and USSR to deal responsibly with world problems; US or USSR more likely to use military force; US or USSR more willing to negotiate disputes with other countries; US or USSR comparable strength in nuclear weapons; risk and equality of nuclear weapons holdings by superpowers; respondent's reading on recent efforts by US and USSR to reach nuclear arms control agreement; US or USSR to blame for failure to reach such an agreement. Standard variables include Federal voting intention, household size, age, marital status, schooling, occupation of respondent or of main income earner, household income, country of birth, industry sector, religion, tenure of dwelling, sex, area. This study is part of a series (SSDA No's 525 to 532) commissioned by the United States Information Service between 1982 and 1985 on Australians' attitudes to defence issues. Similar studies were carried out in New Zealand at the same time (SSDA No's 521 to 524) which contain some parallel questions.